2014
DOI: 10.1055/s-0034-1370790
|View full text |Cite
|
Sign up to set email alerts
|

Instability of the Vertebrae Remains following Balloon Kyphoplasty

Abstract: Study Design Retrospective cohort study. Objectives The mechanism underlying the pain relief observed following balloon kyphoplasty (BKP) to vertebral compression fractures is reported to involve stabilization of the fractured vertebrae. However, whether fixation of the vertebrae was achieved immediately after BKP has not been investigated. The purpose of this study was to assess fixation of the vertebrae immediately after BKP and whether the instability was related to visual analog scale (VAS) scores. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It was previously reported that instability of the vertebrae remained in 45% of cases immediately after BKP. 10 In this study, 9 vertebrae (25%) exhibited instability at the final follow-up examination. Attention should be paid to this finding in order to avoid the development of complications due to remaining instability.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…It was previously reported that instability of the vertebrae remained in 45% of cases immediately after BKP. 10 In this study, 9 vertebrae (25%) exhibited instability at the final follow-up examination. Attention should be paid to this finding in order to avoid the development of complications due to remaining instability.…”
Section: Discussionmentioning
confidence: 56%
“…Past literature previously reported that instability remains after balloon kyphoplasty. 10 Ohba et al 12 reported that instability of the treated vertebrae after balloon kyphoplasty caused paraparesis. In addition, Kim et al 11 reported that the incidence of recompression in treated vertebrae was 12.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focal kyphosis angle between the higher endplate of the upper vertebral body and the lower endplate of the lower vertebral body was measured as previously reported [ 8 , 16 ]. The ratio of occupation by bony fragments of the spinal canal was calculated as the ratio of the bony fragment diameter to the adjacent normal canal diameter on mid-sagittal MR images, as previously reported [ 5 ].…”
Section: Technical Reportmentioning
confidence: 99%
“…Although the BKP procedure can support the anterior vertebral elements, the past literature previously reported that instability remains after BKP [ 8 ]. Spinal stability is ensured by the stability of each of the anterior and posterior elements.…”
Section: Introductionmentioning
confidence: 99%